Penilaian Kondisi Teknik Penangkapan Ikan Lemuru (Sardinella lemuru) Berdasarkan Pendekatan EAFM di PPI Kedonganan, Bali - Atanasius Jenarut; Nyoman Dati Pertami; Made Ayu Pratiwi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2022)
Ecosystem Approach to Fisheries Management (EAFM) is a management concept through an integrated and ecosystem-based approach. This study aimed to describe the condition of Bali Sardinella (Sardinella lemuru) at Kedonganan Fish Port and assess the management of this species based on the EAFM fishing technique domain. The assessment method refers to the methodology used by the National Working Group on EAFM, Directorate of Fish Resources, Ministry of Marine Affairs and Fisheries of Republic Indonesia, 2014. Data analysis used a Likert score based on ordinal 1, 2, 3 against indicators such as destructive/illegal fishing methods, modification of fishing gear, fishery capacity and fishing effort, fishing selectivity. Then, function suitability indicators and size of the ship is fishing boat crew certification adjusted to the status of Kedonganan fish port. Kedonganan fish port was a small- scale fishery. The scores obtained for each indicator was destructive/illegal fishing methods get a score of 2, modification of fishing gear get a score of 1, while indicators of fishery capacity and fishing effort and fishing selectivity get a score of 3. Lemuru fisheries management at Kedonganan fish port technical classified as good with the composite value of 69.